Perspectives from the Edge: Chaplains in Greater Boston, 1945–2015. Issue 1 (22nd January 2019) - Cadge, Wendy; Wang, Katherine; Rowe, Mary
Abstract: We follow Bender et al.'s (Religion on the Edge: De‐Centering and Recentering the Sociology of Religion) call to study religion "on the edge" by looking at the work of chaplains, religious professionals who work outside of congregations. Rather than studying chaplains within a single type of institution—the military, healthcare, or other sectors—we shift the unit of analysis to geography, asking where chaplains in Greater Boston worked between 1945 and the present. Based on coverage in the Boston Globe, we find that chaplains, mostly men, worked across Greater Boston between 1945 and 2015. The majority were Catholic with frequent minorities of Protestants and Jews, and—after 1995—a few Buddhists, Muslims, and Humanists. Most worked in higher education, healthcare, and prisons. While much of the chaplains' work seems improvisational and varied, we identify services related to ceremonies, bearing witness, and working around death as common occurrences across the venues where chaplains worked. To the extent that these patterns are evident in other cities, they suggest that chaplains have regularly been a quiet part of the religious landscape, that they are a consistent part of the institutional field, and that their work has more commonalities across sectors than previous studies suggest.